ANALISIS TINGKAT KEPUASAN PENGUNJUNG TERHADAP KUALITAS PELAYANAN MUSEUM GUNUNGAPI MERAPI DENGAN METODA IMPORTANCE PERFORMANCE ANALYSIS - , Chusnul Chotimah, Dr. Mamduh M. Hanafi, M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research was conducted at Merapi Volcano Museum DIY. Visitor satisfaction is determined by the good service quality, on the purpose of giving satisfaction to visitiors the museum manager should know which things were important to visitors in order to strive for the best possible performance. This research aimed to determine the level of visitor satisfaction on the service quality of Merapi Volcano Museum, and knowing what service indicators needed to be improved and maintainade by the the Merapi Volcano Museum to make it better. The analysis method used in this research is called Importance Performance Analysis (IPA). The research uses probability sampling, the systematic sampling. It uses primary data obtained from the deployment questionnaires of 79 selected respondents. The results showed that the level of customer satisfaction index on the services quality of Merapi Volcano Museum is quite high at 77,73 percent, it means visitors are satisfied with the performance of the Merapi Volcano Museum. Indicator whinch fall into quadrant A require special attention by the management to be improved are the attractiveness and comfort of the interior room décor, indicators in quadrant B that have be maintained consist of the amount of space or visitors, the speed of service to visitors, staff willingness to help, convenient hours of operation, and the attitude of officials in contact with the visitors.